Rural Infrastructure in Nepal: A Critical Scrutiny - Acharya, Umesh (Nepalese Journal of Development and Rural Studies, 2022)
The objective of this paper is to analyse the role of rural infrastructure in the development of Nepal. Secondary data collected from various sources have been used retrieving them from different publications of government departments, engineering institutes and libraries besides other demonstrated materials from different researches of rural infrastructures programmes. The finding of this paper is that developmental programmes that focus on the rural location play a vital role in the development of Nepal. Some works related to rural infrastructures had been implemented and some works are being processed for implementation in the future.